Intelligent wearable : early designers / Zolina Mohamad, Norzaleha Zainun and Suriati Saidan - Mohamad, Zolina; Zainun, Norzaleha; Saidan, Suriati (Universiti Teknologi MARA, Perak, 2020)
It is an overview of the significant landmark in techno fashion landscape. Although the narrative would be on electronic and digital technology in fashion, writer is keen on specifying it on intelligent wearable and the pioneering designers who made the ground-breaking debuts. Intelligent wearable is one of many prominent constituents in techno fashion diaspora. It has a significant role in shaping the future world of contemporary fashion by converging art and science.